2016
DOI: 10.4103/0972-5229.178183
|View full text |Cite
|
Sign up to set email alerts
|

Brain lesions in eclampsia: A series of 39 cases admitted in an Intensive Care Unit

Abstract: The aim of this study was to identify the encephalic lesions in the eclampsia occurrences. Within a period of 18 months, computed tomography (CT) of the brain was performed in all patients admitted in intensive care for eclampsia. These CTs were analyzed and intracerebral lesions were identified. Thirty-nine patients were included. We noted 10 cases of ischemic stroke, 9 cases of cerebral edema, and 3 cases of hemorrhagic stroke and subarachnoid hemorrhage. The CT scan came back to normal in 20 eclamptic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
2
4
1
Order By: Relevance
“…The presentation of stroke alone prevailed over the combinations (58.33% vs 41.66%), the proportion was 1.4. The stroke combinations in the same patient has also been reported by Harandou, [18] Jaigobin et al [23] and Brouh et al [24]. The comparison of the hemodynamic and clinical laboratory data did not show any substantive difference to explain the clinical behavior of stroke (Tables 2 and 4).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The presentation of stroke alone prevailed over the combinations (58.33% vs 41.66%), the proportion was 1.4. The stroke combinations in the same patient has also been reported by Harandou, [18] Jaigobin et al [23] and Brouh et al [24]. The comparison of the hemodynamic and clinical laboratory data did not show any substantive difference to explain the clinical behavior of stroke (Tables 2 and 4).…”
Section: Discussionsupporting
confidence: 80%
“…The location of the lesions varied: parietal, parietal-frontal, parieto-frontooccipital, occipital, and in the territory of the middle cerebral artery. Brouh et al [24] and Beye et al [25] did not identify venous lesions, in the present investigation the stroke of venous origin appeared in a significant percentage of cases 41.66%, thrombosis of the superior longitudinal sinus was the only site of venous lesion. Coutinho et al [9] carried out a systematic review of venous stroke in both women and men and concluded that its incidence is higher in women, the difference lies in the complications of pregnancy and puerperium.…”
Section: Discussioncontrasting
confidence: 46%
“…A very rare complication is DIC and/or postpartum subarachnoid hemorrhage can transpire in a patient with HELLP syndrome undergoing spinal anesthesia. Though experimental, a bolus of remifentanil has shown promising effects but is limited due to the risk of neonatal depression [5,29,30]. The diagnosis is clinically based, with the added combination of CT visualization of increased density within regions of the brain, leading to a correlated diagnosis showing vascular brain bleeds in conjunction with neurological deficits [9,17].…”
Section: Discussionmentioning
confidence: 99%
“…A very rare complication is DIC and/or postpartum subarachnoid hemorrhage can transpire in a patient with HELLP syndrome undergoing spinal anesthesia. Though experimental, a bolus of remifentanil has shown promising effects but is limited due to the risk of neonatal depression [ 5 , 29 , 30 ]. The diagnosis is clinically based, with the added combination of CT visualization of increased density within regions of the brain, leading to a correlated diagnosis showing vascular brain bleeds in conjunction with neurological deficits [ 9 , 17 ].…”
Section: Discussionmentioning
confidence: 99%